Photoecology of the Antarctic cyanobacterium Leptolyngbya sp. BC1307 brought to light through community analysis, comparative genomics and in vitro photophysiology. Issue 24 (31st December 2018) - Chrismas, Nathan A. M.; Williamson, Christopher J.; Yallop, Marian L.; Anesio, Alexandre M.; Sánchez‐Baracaldo, Patricia
Abstract: Cyanobacteria are important photoautotrophs in extreme environments such as the McMurdo Dry Valleys, Antarctica. Terrestrial Antarctic cyanobacteria experience constant darkness during the winter and constant light during the summer which influences the ability of these organisms to fix carbon over the course of an annual cycle. Here, we present a unique approach combining community structure, genomic and photophysiological analyses to understand adaptation to Antarctic light regimes in the cyanobacterium Leptolyngbya sp. BC1307. We show that Leptolyngbya sp. BC1307 belongs to a clade of cyanobacteria that inhabits near‐surface environments in the McMurdo Dry Valleys. Genomic analyses reveal that, unlike close relatives, Leptolyngbya sp. BC1307 lacks the genes necessary for production of the pigment phycoerythrin and is incapable of complimentary chromatic acclimation, while containing several genes responsible for known photoprotective pigments. Photophysiology experiments confirmed Leptolyngbya sp. BC1307 to be tolerant of short‐term exposure to high levels of photosynthetically active radiation, while sustained exposure reduced its capacity for photoprotection. As such, Leptolyngbya sp. BC1307 likely exploits low‐light microenvironments within cyanobacterial mats in the McMurdo Dry Valleys.